VariScreen secures the screening of high-risk varices in patients with hepatitis B virus-related cirrhosis beyond Baveno VI criteria - Tan, Min; Zhang, Wuxiang; Zhou, Hong; Liu, Yujuan; Lu, Tao; Zhang, Yin; Li, Chuan; Yang, Yanyan; Wu, Yunchong; Hu, Han; Li, Ying; Yang, Fangwan; et al. (Frontiers in Physiology, 2022)
We aimed to validate the performance of the ratio of the platelet count (PLT) to liver stiffness measurement (LSM) in excluding high-risk varices (HRVs) in patients with hepatitis B virus (HBV)-related compensated cirrhosis beyond Baveno VI criteria. A total of 310 patients were assessed. The performances of the PLT:LSM ratio (PLER), PLER adjusted for the International Normalized Ratio, etiology, age, and sex (PLEASE), and the sequential algorithm for HRV screening (VariScreen) in excluding HRVs were evaluated and compared with those of expanded Baveno VI criteria (LSM <25 kPa and PLT >110×109/L, EB6C); PLT >150×109/L and model for end-stage liver disease score = 6 (P150M6 criterion); PLT >120×109/L and albumin >36 g/L (P120A36 criterion); and albumin-bilirubin (ALBI) grade and PLT score (ALBI-PLT score). Among enrolled patients, 43 (13.9%) had HRVs. The area under the receiver operating characteristic curve of PLER for predicting HRVs (0.771, 95% confidence interval, 0.720–0.817) was significantly higher than that for PLT and LSM (P<0.01). PLER was an independent risk factor for HRVs. VariScreen, PLEASE, and PLER could spare 20 (6.5%), 91 (29.4%), and 60 (19.4%) endoscopies, with 0, 3 (3.3%), and 1 (1.7%) HRVs missed, respectively. The EB6C and P120A36 criteria could spare 45 (14.5%) and 36 (11.6%) endoscopies, with 1 (2.2%) and 1 (2.8%) HRVs missed, respectively. The P150M6 criterion and ALBI-PLT score missed 6.8% and 10.3% of HRVs. We found that PLER performed better than the other non-invasive tested. VariScreen secured the screening of HRVs in patients with HBV-related cirrhosis beyond Baveno VI criteria.